2017
DOI: 10.1371/journal.pone.0184742
|View full text |Cite|
|
Sign up to set email alerts
|

Iron deficiency was not the major cause of anemia in rural women of reproductive age in Sidama zone, southern Ethiopia: A cross-sectional study

Abstract: BackgroundAnemia, which has many etiologies, is a moderate/severe public health problem in young children and women of reproductive age in many developing countries. The aim of this study was to investigate prevalence of iron deficiency, anemia, and iron deficiency anemia using multiple biomarkers and to evaluate their association with food insecurity and food consumption patterns in non-pregnant women from a rural area of southern Ethiopia.MethodsA cross-sectional study was conducted in 202 rural women of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
4
27
2
Order By: Relevance
“…In this study, iron deficiency was fairly high (31%) and prevalence of anemia was 19%, which was slightly lower than the 21% previous reported for women of reproductive age in the same study area [30]. However, iron deficiency anemia was only 7%.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In this study, iron deficiency was fairly high (31%) and prevalence of anemia was 19%, which was slightly lower than the 21% previous reported for women of reproductive age in the same study area [30]. However, iron deficiency anemia was only 7%.…”
Section: Discussioncontrasting
confidence: 73%
“…Mothers in food insecure households are more likely to be undernourished than mothers in food secure households [49]. However, in our previous study food insecurity was not a significant predictor of low hemoglobin in women of reproductive age [30].…”
Section: Plos Onementioning
confidence: 53%
“…In the current meta-analysis 13.6% of among pregnant women in Sudan had IDA. This rate (13.6%) of IDA was higher than the rate (5%) of IDA reported among rural women of reproductive age in southern Ethiopia [ 43 ]. However, 20.7% of pregnant women in Niger had IDA [ 36 ].…”
Section: Discussionmentioning
confidence: 63%
“…This was also in line with findings of Gebreegziabher and Stoecker in southern Ethiopian women of reproductive ages. Using multiple iron biomarkers, the authors found only 5% of iron deficiency anemia from 21.5 total anemic cases identified, supporting that iron deficiency may not be a major contributor of anemia in Ethiopia pregnant women as it is predicted before[37]. This suggests the need to consider anemia attributable to factors other than an iron deficiency in designing effective public health intervention program for anemia control.…”
Section: Discussionmentioning
confidence: 82%